Human metapneumovirus in lung transplant recipients: characteristics and outcomes. Issue 11 (1st December 2016) - Niggli, Fabian; Huber, Lars C.; Benden, Christian; Schuurmans, Macé M.
Abstract: Human metapneumovirus (hMPV) causes serious respiratory tract infections in lung transplant recipients (LTRs). We evaluated the characteristics and adverse drug reactions (ADR) of oral ribavirin therapy for hMPV infections in LTRs. LTRs with respiratory symptoms or suspected infection of unknown origin were routinely sampled with nasopharyngeal swabs (NPS) for virological and bacteriological analysis as part of a diagnostic workup. Medical records of hMPV polymerase chain reaction (PCR)-positive LTRs at the University Hospital of Zurich were reviewed retrospectively. Between January 2012 and June 2014, 12 (80%) of 15 consecutive patients with documented hMPV infection received oral ribavirin therapy (800 mg/d, after 48 h: 400 mg/d). Mean duration of therapy was 28.6 days (range: 11–54). Mean duration of viral shedding was 16.3 days (range: 5–48). In general, oral ribavirin was well tolerated in LTRs. The most common ADR was moderate anaemia. All patients recovered from infection without immediate serious sequelae within 3 months of infection.